TINJAUAN SYSTEMATIC REVIEW : PENGARUH PEMBERIAN EKSTRAK BUAH SEMANGKA (Citrullus Lanatus) TERHADAP KUALITAS SPERMATOZOA TIKUS PUTIH (Rattus Norvegicus) GALUR WISTAR DENGAN STRESS OKSIDATIF - Fifih Febriyani, (2023)
Oxidative stess may lower spermatozoa quality and cause infertility. Infertility is the condition in where a man and woman are unable to produce a child after doing intercourse without contraception for 12 months. Oxidative stress is prevented by increasing the consumption of antioxidants such as Citrullus Lanatus (Watermelon Fruit). Watermelon fruit contain antioxidants like flavonoid and lycopene that reduce the occurance risk of oxidative stress. This research aims to analyze the effects of watermelon extracts (citrullus lanatus) on galur wistar rat's (Rattus norvegicus) sperm quality, with or without oxidative stress. Methods: This research uses the systematic literature review method. The compiling of journal used in this research was done from May to June 2022. The search used database from Google Scholar, pubmed, and mendeley which afterwards undergoes a selection process using PRISMAP. Journal assesment were done using JBI (Joanna Briggs Institute) based Quality Assesment. Result: This research found 8 journal that, with the addition of Citrullus lanatus, there is an increase and recovery in spermatozoa quality with or without oxidative stress. These 8 journal consist of 5 journal with research on sperm quantity, 2 journal with research on sperm concentration, 5 journal with research on sperm motility, 4 journal with research on sperm morphology, 7 journal with reseach on testosterone level, 5 journal with research on FSH and LH level, and 6 journal with research on Histology of sperm. Conclusion: Citrullus lanatus contain lycopene and flavonoid that can increase and repair spermatozoa quality with or withour oxidative stress.